Happily partnered older adults' relationship‐enhancing behaviours. (21st June 2020) - Rahn, Alison; Bennett, Cary; Jones, Tiffany; Lykins, Amy
Abstract: Objective: Relationship‐enhancing behaviours that contribute to older adults' well‐being are scarcely considered in "active ageing" discourses despite relationship quality having been repeatedly linked to health outcomes. This paper explores such behaviours in older adults. Methods: Cross‐sectional data were collected in 2016 from 168 partnered baby boomers (born 1946 to 1965) using an online survey. The 36 qualitative and quantitative questions were analysed using mixed methods. Results: Participants were predominantly women (85%), with a mean age of 62 years (SD = 5.2). Relationship‐enhancing behaviours included verbal and non‐verbal cues, physical affection and pleasurable sexual activities. A couple's shared bed was an important relationship setting. Conclusion: For happily partnered older adults, relationship quality improves personal well‐being. As a social determinant of healthy ageing, health policies and programs are needed to support older adults' relationship quality. To this end, the development of targeted relationship interventions for delivery in health settings is warranted.